Condition assessment of high voltage insulation in power system equipment - James, R. E.; Su, Qi (Institution of Engineering and Technology, 2008)
The book reviews developments in the following fields: insulating material; power system equipment; electrical insulation design; insulation testing; sensors; online insulation condition monitoring technique; artificial intelligence techniques; and fault diagnosis.